1986
DOI: 10.1346/ccmn.1986.0340511
|View full text |Cite
|
Sign up to set email alerts
|

Supergene Vermiculitization of A Magnesian Chlorite: Iron and Magnesium Removal Processes

Abstract: Abstract--An X-ray powder diffraction study of a verrniculitized chlorite in an amphibole schist near Limoges, France, shows the following weathering sequence: chlorite ~ ordered interstratified chlorite/ vermiculite ~ vermiculite. M6ssbauer spectroscopy indicates that vermiculitization proceeded by the release of ferrous iron from the 2:1 mica layer of the chlorite. The ferric iron content of the vermiculite product is almost the same as that of the initial chlorite. Infrared spectroscopy and chemical micropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 31 publications
(31 reference statements)
5
29
0
2
Order By: Relevance
“…These substitutions occur to compensate for the excess of negative charges in the mica-like layers. This vermiculitization process is in good agreement with currently accepted weathering mechanisms (e.g., Proust et aL, 1986;Fordham, 1990bFordham, , 1990c. In the late stage of the vermiculitization of phlogopite, these substitutions change to a slight increase of A1 for Si in tetrahedral positions.…”
Section: Consideration Of Structural Formula For Vermiculitesupporting
confidence: 88%
“…These substitutions occur to compensate for the excess of negative charges in the mica-like layers. This vermiculitization process is in good agreement with currently accepted weathering mechanisms (e.g., Proust et aL, 1986;Fordham, 1990bFordham, , 1990c. In the late stage of the vermiculitization of phlogopite, these substitutions change to a slight increase of A1 for Si in tetrahedral positions.…”
Section: Consideration Of Structural Formula For Vermiculitesupporting
confidence: 88%
“…However, as pointed out earlier, neither corrensite nor Mg-rich chlorite has ever been described from modern evaporitic environments (Bodine and Madsen, 1987). Ordered regularly interstratiffed corrensite-like minerals have frequently been described from the weathering environment (Johnson, 1964;Proust et al, 1986); but it is almost certainly misleading to group these minerals with diagenetic corrensites. For instance, Wilson and Nadeau (1985) have argued that interstratified clays formed by transformation from coarse grained phyllosilicates during weathering are fundamentally different from the fine grained interstratified clays formed during diagenesis.…”
Section: Origin Of Chlorite Minerals In the 'Evaporite Carbonate" Assmentioning
confidence: 99%
“…Chlorite can be transformed to vermiculite when the hydroxide sheet is disrupted by thermal dehydroxyl-ation or low-temperature acid leaching (Ross and Kodama, 1974;Bain, 1977;Proust et aL, 1986;Wilson, 1986). The removal of iron from the chlorite hydroxide sheet is an essential part of the process, and a high iron concentration in the hydroxide sheet appears to be a necessary prerequisite for chlorite vermiculitization.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of iron from the chlorite hydroxide sheet is an essential part of the process, and a high iron concentration in the hydroxide sheet appears to be a necessary prerequisite for chlorite vermiculitization. The iron can be oxidized (Makumbi and Herbillon, 1972;Ross, 1975) or unoxidized (Proust et al, 1986) by the vermiculitization process, and sedimentary goethite is sometimes reported as a reaction product (Anand and Gilkes, 1984).…”
Section: Introductionmentioning
confidence: 99%